2017
DOI: 10.1103/physrevb.96.075307
|View full text |Cite
|
Sign up to set email alerts
|

Spin polarization and exchange-correlation effects in transport properties of two-dimensional electron systems in silicon

Abstract: We show that the parallel magnetic field-induced increase in the critical electron density for the Anderson transition in a strongly interacting two-dimensional electron system is caused by the effects of exchange and correlations. If the transition occurs when electron spins are only partially polarized, additional increase in the magnetic field is necessary to achieve the full spin polarization in the insulating state due to the exchange effects.PACS numbers: 71.10.-w, 71.27.+a, 71.30.+h The metal-insulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 42 publications
3
13
0
Order By: Relevance
“…Another effect of the parallel magnetic field is that it wipes out the strong metallic temperature dependence of the resistance at electron densities just above n c and suppresses the metallic regime [7,17,19,[25][26][27]. In Fig.…”
Section: Influence Of the Magnetic Field Parallel To The 2d Planementioning
confidence: 99%
“…Another effect of the parallel magnetic field is that it wipes out the strong metallic temperature dependence of the resistance at electron densities just above n c and suppresses the metallic regime [7,17,19,[25][26][27]. In Fig.…”
Section: Influence Of the Magnetic Field Parallel To The 2d Planementioning
confidence: 99%
“…It is interesting to compare the ratio n c (B * )/n c (0) ≈ 1.2 of the measured critical densities for the MIT to that calculated in Ref. [28]. According to the calculations, the increase of the critical electron density for the Anderson transition in a strongly interacting 2D electron system with increasing B is due to the exchange and correlation effects, and the ratio between the critical electron densities for fully spin-polarized and unpolarized electron systems is independent of the density of impurities and is equal to ≈ 1.33.…”
Section: Introductionmentioning
confidence: 79%
“…In the zero field MIT, it was established that an in-plane magnetic field causes large positive magneto-resistance and drives the system toward the insulating phase [8,9,42,43]. Recent in-plane field magneto-transport experiments revealed that the resistivity of dilute 2D electrons in Si-MOSFET in the insulating state are the same for zero field and in the presence of an in-plane field that polarizes the spins [43], a behavior different from the metallic phase of the 2D MIT [8,9,42]. It would be thus very insightful to study the effect in-plane magnetic field induced spinpolarization effect on the RIPs and examine how the in-plane field affects the transition between the RIPs and metallic liquid.…”
Section: Discussion and Outlookmentioning
confidence: 99%